Elucidating specificity of an allosteric inhibitor WNK476 among With‐No‐Lysine kinase isoforms using molecular dynamic simulations. (5th June 2021) - Amarnath Jonniya, Nisha; Sk, Md Fulbabu; Kar, Parimal
Abstract: Specifically targeting the With‐No‐Lysine (WNK1) kinase, which is implicated in hypertension, renders a significant challenge in discovering competitive inhibitors due to the highly conserved ATP‐binding pocket. However, an allosteric inhibitor may impart high specificity against the WNK kinase isoforms since it targets the less conserved site and can provide greater efficacy even under high physiological ATP concentration. In the current study, we have investigated the structural and energetic basis of the specificity of the allosteric inhibitor WNK476 against WNK kinase isoforms by combining molecular dynamics simulations and free energy calculations using molecular mechanics Poisson–Boltzmann surface area. Our study reveals that the conformational stabilization of αC‐helix near the allosteric binding site, including conformational changes in activation and glycine‐rich loop regions, favors the specificity of WNK476 toward WNK1. The MM/PBSA calculations suggest that the non‐polar contribution from hydrophobic residues and polar solvation energy influences WNK/WNK476 complexation. Despite more favorable electrostatic and van der Waals interactions in WNK2/WNK476, WNK476 is more potent against WNK1 due to the lower contribution of disfavoring components—polar solvation and entropy. Further, we have identified that the hydrophobic residues of DLG, αC‐helix, β4, and β5 regions, and H‐bond network near the β4 strand play a critical role in the specificity of WNK476 against WNK1. Finally, our study reveals that residues Leu 272, Val 281, Phe 283, and Leu 369 of WNK1 actively contribute to the overall hydrophobic interactions for WNK1/WNK476. Overall, our study might help in the rational design of novel allosteric inhibitors against hypertension. Abstract : The study reveals that the conformational stabilization of the αC‐helix near the allosteric binding pocket and conformational rearrangements of the activation and glycine‐rich loop regions favor the specificity of WNK476 against WNK1 compared to other isoforms.